Fungsi dan Aplikasi Motivasi dalam Pembelajaran - Farida, Nur (Universitas Muslim Indonesia, 2021)
The purpose of this research is to identify the factors that drive motivation, as well as the role of motivation in teaching and learning. This is a qualitative study conducted using library research methods. Work motivation is a driving force and source of encouragement that can elicit a sense of zeal, as well as modify human or individual behavior to lead to improved outcomes. Motivation is defined as the overarching driving force within the instructor that initiates and directs instructional actions in order to attain the objectives set forth by the teaching subject. So that every teacher is diligent in completing assignments, tenacious in overcoming obstacles (not easily discouraged), shows interest in a variety of problems, prefers to work independently, is not easily bored with routine tasks, is able to defend his or her point of view, and enjoys finding and solving problems.